Serological Findings in a Child with Paroxysmal Cold Haemoglobinuria - Eduardo J. Salido; Valentín Cabañas; Mercedes Berenguer; María I. Macizo; Faustino García-Candel; Raúl Pérez-López; Jose M. Moraleda (Case Reports in Medicine)
PCH is a rare autoimmune hemolytic anemia (AIHA) but is one of the most common causes of AIAH in children. For the diagnosis, it is important to perform the appropriate methods of serological investigation and show the typical biphasic reaction. This is a case report of a child who presented with features of haemolysis and was diagnosed with PCH of this way.